Develop Your CORE2 for Career Flourishing: A Career Development Workshop for Hospitalists - Ryan E. Nelson; Emily A. Mallin; Shannon K. Martin (Association of American Medical Colleges, 2024)
Introduction Appreciative inquiry harnesses an individual's strengths to realize positive change, and a flourishing-focused mindset emphasizes engagement, social connectivity, and seeking meaningful work. Though the impact of these models on physician well-being and career planning has been evaluated in graduate medical education, their integration into career development initiatives for faculty has been limited. We designed a workshop to nurture hospitalist career development, based on our CORE2 conceptual framework (character strengths, overall vision, role assessment, explicit goals, and evaluation). Methods We presented the workshop at the 2022 and 2023 Society of Hospital Medicine (SHM) annual conferences. This 1.5-hour workshop comprised four modules and three small-group activities designed to help participants identify their signature character strengths, draft a professional vision statement, prioritize professional roles, and develop SMART goals aligned with these roles. Results At the 2023 SHM annual conference, 36 participants attended the workshop, and 32 (89%) completed pre- and postworkshop surveys. After workshop completion, participants' self-assessed familiarity with their signature character strengths, knowledge of evidence-based principles to develop SMART goals, and confidence in their ability to write a vision statement and SMART goals all increased significantly (p < .05). Discussion This workshop provides a valuable framework for self-directed longitudinal career development and reflection. We build on prior curricula on educator identity formation by guiding participants from identity definition to professional vision development to professional role evaluation to aligned goal creation and iterative evaluation. Our workshop's principles are readily generalizable to clinician-educators across medical disciplines.